Correction strategy for wear-out prediction of PV inverters considering the mission profile resolution effects. (August 2022) - Silva, R.P.; de Barros, R.C.; Boaventura, W.C.; Cupertino, A.F.; Pereira, H.A.
Abstract: In literature, there are reliability studies on electrical power systems with several mission profile (MP) resolutions. Although high-resolutions MPs represent more accurately the actual behavior of the system operating conditions, they are more difficult to be correctly recorded and lead to lifetime simulations with high computational burden. In this context, low-resolution MPs are an interesting alternative to solve these issues. However, previous works have concluded that the decreased MP resolution modifies the dynamics of the actual mission profile, which inevitably affects the wear-out prediction accuracy of power converters. Thus, this work proposes a correction strategy to reduce the errors in the lifetime consumption ( LC ) estimations of a single-phase grid-connected photovoltaic (PV) inverter due to the MP resolution decreasing. Primarily, the strategy aims to determine a correction equation which is able to reduce the deviations in the LC estimations of a PV inverter when MPs with different sampling time values are used in the lifetime evaluation procedure. The results demonstrate that the correction equation determined by the proposed strategy improves the lifetime evaluations for the considered low-resolution MPs. In addition, the determined equation proved to be adaptable to the characteristics of solar irradiance and ambient temperature of different regions of the word. Highlights: Proposing of a methodology to determine a correction equation which is able to reduce the errors in the lifetime consumption estimations of a specific PV inverter caused by the mission profile resolution decreasing; Determination of a correction equation adaptable to the characteristics of solar irradiance and ambient temperature of different regions of the world.